2010
DOI: 10.1016/j.jasms.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase fragmentation characteristics of benzyl-aminated lysyl-containing tryptic peptides

Abstract: The fragmentation characteristics of peptides derivatized at the side-chain -amino group of lysyl residues via reductive amination with benzaldehyde have been examined using collision-induced dissociation (CID) tandem mass spectrometry. The resulting MS/MS spectra exhibit peaks representing product ions formed from two independent fragmentation pathways. One pathway results in backbone fragmentation and commonly observed sequence ion peaks. The other pathway corresponds to the unsymmetrical, heterolytic cleava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The loss of a molecule of water from the complementary fragment ion at m / z 106 is very likely at the origin of the m / z 88 ion signal (Scheme ). Reports on the benzylic dissociation in the case of diarylpyrimidines, benzyl esters and thioethers are available in the literature . The MS/MS spectrum reported by Feng et al .…”
Section: Resultsmentioning
confidence: 99%
“…The loss of a molecule of water from the complementary fragment ion at m / z 106 is very likely at the origin of the m / z 88 ion signal (Scheme ). Reports on the benzylic dissociation in the case of diarylpyrimidines, benzyl esters and thioethers are available in the literature . The MS/MS spectrum reported by Feng et al .…”
Section: Resultsmentioning
confidence: 99%
“…In electrospray ionization mass spectrometry (ESI-MS), fragmentation of benzylated cations prefers to generate benzyl cations [7,8,[20][21][22][23][24][25][26][27][28][29][30], though a few exceptions have been reported that tropylium ion can be co-produced in the fragmentation of benzylpyridinium ions [18,31,32]. Besides the formation of benzyl cations, other interesting ions resulting from hydride transfer [24,25] or electrophilic aromatic substitution reactions [20][21][22] via the nonconventional ion/neutral complex (INC) can also be generated in the dissociation of benzylated cations.…”
Section: Introductionmentioning
confidence: 99%
“…Benzyl cations are highly reactive intermediates in various chemical and biochemical reactions and usually short‐lived in solution . In an INC, benzyl cations formed during the CID process may lead to hydride transfer, electron transfer, proton transfer, electrophilic aromatic substitution and nucleophilic aromatic substitution …”
Section: Introductionmentioning
confidence: 99%